Manajemen Mutu Program Kallimni pada Kelas Online Kursus Bahasa Arab Al-Azhar Pare - Ahmad Azhari; Gesbi Rizqan Rahman Arief; Danial Hilmi (Institut Agama Islam Negeri Metro, 2022)
The purpose of this study is to describe the quality management in the Kallimni program which is applied by the Al-Azhar Pare language course institution in online classes. The method used in this research is descriptive qualitative. Data were collected with several instruments, namely observation, interviews, and documents. Data is analyzed through data condensation, data presentation, and data verification. The results of the study indicate that quality management in the Kallimni program of online Arabic classes at the Al-Azhar Pare course institution includes planning, implementation, and evaluation. The planning stage is carried out through the SWOT (Strength, Weakness, Opportunity, Threath) stages. So that the quality and quality of the online class program can be well maintained during the online learning period. In its implementation, all components contained in the program are always considered, in order to avoid any discrepancies with what has been planned. Likewise in quality evaluation, all aspects of the curriculum are monitored, so that the quality and quality of online class programs can be well maintained during online learning. It is hoped that the research can contribute to both formal and non-formal educational institutions as a reference in quality management.